2019
DOI: 10.31129/lumat.7.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service mathematics teachers’ beliefs regarding topics of mathematics education

Abstract: Beliefs are known to influence learning processes and thus become relevant in the instruction of pre-service mathematics teachers with regard to the pedagogical content knowledge taught in courses of mathematics didactics at university. In exploring beliefs about mathematics didactics of pre-service teachers training for secondary school, 50 bachelor students (ca. 5th semester) responded to two open-ended tasks in which they were asked to express their understanding of mathematics didactics. With the help of q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Beliefs are part of the affective domain of an individual that influences the learning process ( Manderfeld and Siller, 2019 ). Understanding young students’ emotional factors and beliefs about mathematics is a complex task ( Giaconi et al, 2016 ), as is understanding teachers’ perceptions of mathematical problem solving and its teaching.…”
Section: Methodsmentioning
confidence: 99%
“…Beliefs are part of the affective domain of an individual that influences the learning process ( Manderfeld and Siller, 2019 ). Understanding young students’ emotional factors and beliefs about mathematics is a complex task ( Giaconi et al, 2016 ), as is understanding teachers’ perceptions of mathematical problem solving and its teaching.…”
Section: Methodsmentioning
confidence: 99%
“…The findings of the studies show that there is a considerable positive link between belief and PCK. Beliefs have been shown to influence learning processes, making them relevant in the preparation of pre-service mathematics instructors in terms of the PCK provided in university-level mathematics didactics courses (Manderfeld & Siller, 2019). Another study stated that teachers' content knowledge and beliefs about TnL are important elements in effective teaching and, as a result, in student achievement (Ekmekci et al, 2019).…”
Section: Beliefmentioning
confidence: 99%
“…The results of the study detailing professional development showed a good effect on PCK. For instance, professional development programs (Ekmekci et al, 2019;Hidayat & Setyawan, 2020;Maboya et al, 2022;Sarkim, 2020), content-focused professional development (Richter et al, 2021), model/ professional training/ teacher training/ collaboration programs (Gambini & Lenart, 2021;Jeschke et al, 2021;Kurt-Birel et al, 2020;Manderfeld & Siller, 2019;Saputra et al, 2019;Sunzuma & Maharaj, 2019;Tang, 2018;Yildiz & Akyuz, 2019;Yilmaz & Demir, 2021), seminar/ workshops/ in-service training (Ansah et al, 2020;Chang et al, 2020;Kurt-Birel et al, 2020;Moh' d et al, 2021), educational course/ pedagogy course (Lau, 2019;Lee et al, 2018), school based continuous professional development/ on-site professional training (lesson study) (Helmbold et al, 2021;Mhakure, 2019), structured interventions/ professional learning workshops (Hilton & Hilton, 2018), regular meetings (Taylan et al, 2022), microteaching course/ microteaching/ teaching practicums (Setyaningrum et al, 2018) and a two-week summer institute (Schoen et al, 2019) were implemented to enhance mathematics teachers' PCK level effectively. Notably, terms such as model, professional training, teacher training and collaboration program were frequently used to represent professional development in most of the studies.…”
Section: Professional Developmentmentioning
confidence: 99%
“…He indicated that beliefs develop through the individual's membership in the social groups. Manderfeld and Siller(2019) define it as a pool of perceptions that the individuals hold, which are useful, impacting and acquired from the daily experience; or internal inherent in the personality of the individual personality. Rott (2019) adds that the beliefs influence the individual's abilities and direct his decisions about what he believes about the world and the surrounding things.…”
Section: Introductionmentioning
confidence: 99%